The effect of soil ionization on transient grounding electrode resistance in non-homogeneous soil conditions - Mokhtari, M. (John Wiley and Sons Ltd, 2016)
The soil ionization phenomenon effectively reduces the grounding electrode resistance. The existing methods to determine the soil ionization effect on the transient resistance of a grounding electrode are valid only for homogeneous soils. However, most soil structures are non-homogeneous. Realizing the importance of the issue, this study proposes a hybrid method to incorporate the soil ionization effect on the transient resistance of a grounding electrode located in non-homogeneous soil condition. The electromagnetic field approach is utilized to compute the ionized soil volume around the electrode to determine the equivalent radius of the electrode. A circuit-based method of computing the grounding resistance of the electrode in non-homogeneous soil conditions is proposed based on the per-unit-length distributed parameter method. The proposed method is validated by using an electromagnetic field-based numerical solution for the non-homogeneity effect of the soil on grounding electrode resistance.